Successful left coronary cusp cryoablation in an adolescent with premature ventrıcular extrasystoles-associated cardiomyopathy - Yakup Ergül; Senem Özgür; Hasan Candaş Kafalı (KARE Publishing, 2020)
Ventricular arrhythmias arising from coronary cusps are not uncommon. However, the mapping and ablation of outflow tract ventricular arrhythmias originating from aortic cusps can be challenging. Radiofrequency ablation of this area can cause rare but serious complications. This was a report of a 17-year-old male patient with very frequent, nonsustained ventricular tachycardia attacks and premature ventricular contraction-induced cardiomyopathy. The origin of the ventricular arrhythmia was determined to be the left coronary cusp, and the patient was treated successfully with cryoablation. In high-risk areas, cryoablation is an effective and safe alternative method.